2020
DOI: 10.18203/2394-6040.ijcmph20200933
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting internet use among university students in Sarawak, Malaysia: an empirical study

Abstract: Background: The internet has become an indispensable tool for communication, academic research, information and entertainment. However, heavy users of the internet lead to less confidence in social skills and the tendency to be isolated. The study aimed to assess the pattern of internet use and factors affecting problematic internet use among university students.Methods: This cross-sectional study conducted among the students of a university in Sarawak, Malaysia. A multistage cluster sampling technique was ada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
3
1
0
Order By: Relevance
“…In this light, statistically significant relation was found between years of internet accessibility and level of internet addiction. This finding is congruent with the result of a study done by Rahman et al (2020) in Bangladesh who reported that more than half of the studied sample used the internet for less than 5 years with statistically significant relation between years of internet accessibility and level of internet addiction. In contrast, the finding of study done by Saied S et al (2016) in Egypt who reported that less than three quarters of the studied students used the internet for more than 5 years.…”
Section: Discussionsupporting
confidence: 91%
“…In this light, statistically significant relation was found between years of internet accessibility and level of internet addiction. This finding is congruent with the result of a study done by Rahman et al (2020) in Bangladesh who reported that more than half of the studied sample used the internet for less than 5 years with statistically significant relation between years of internet accessibility and level of internet addiction. In contrast, the finding of study done by Saied S et al (2016) in Egypt who reported that less than three quarters of the studied students used the internet for more than 5 years.…”
Section: Discussionsupporting
confidence: 91%
“…In line with previous studies, time spent on online gaming and social media had increased during the lockdown period ( Fernandes et al, 2020 , Sun et al, 2020 ) In the present study, commonly used social media applications were YouTube, Facebook, Instagram, Twitter, and WhatsApp. Consistent with previous studies ( Rahman et al, 2020 ), students tended to use Facebook and Instagram as social networking agents, while WhatsApp became the primary tool for social communication during the lockdown period. YouTube was highly used, possibly as a medium for distance learning ( Kapahi et al, 2013 ) as the students were not able to return to the university for face-to-face teaching.…”
Section: Discussionsupporting
confidence: 85%
“…Our result on the Gaming Addiction Scale showed that only 4.5% (N = 8) of the participants could be defined as monothetic gamers (i.e., “pathological gaming”). A similar prevalence rate was reported by Rahman et al (2020) which found that students less frequently used the internet for online gaming in comparison with social media. A study by Lemmens et al (2009) also using the 7-item Game Addiction Scale reported that 2% of Dutch adolescent gamers met the gaming addiction criteria ( Lemmens et al, 2009 ).…”
Section: Discussionsupporting
confidence: 81%
“…However, there is a lack of evidence for cause-effect relationships between PIU and these negative outcomes (Kubey et al, 2001;Skues et al, 2015). Research continues to suggest that university students who spend longer times on the Internet have been associated with poor academic performance (Caplan, 2002;Niemz et al, 2005;Rahman et al, 2020) and are a group in whom problematic Internet use may manifest as having a direct and quantifiable impact on academic performance (Skues et al, 2015).…”
Section: Problematic Internet Use (Piu)mentioning
confidence: 99%